Association between cerebral blood flow changes and blood–brain barrier compromise in spontaneous intracerebral haemorrhage. Issue 11 (November 2022) - Zhang, X.; Zhu, H.C.; Yang, D.; Zhang, F.C.; Mane, R.; Sun, S.J.; Zhao, X.Q.; Zhou, J.
Abstract : AIM: To quantitatively evaluate blood–brain barrier (BBB) permeability in the perihaematomal region of spontaneous intracerebral haemorrhage (ICH) and investigate the association between the alterations in cerebral blood flow and BBB permeability around the haematoma. MATERIALS AND METHODS: Spontaneous ICH patients underwent unenhanced computed tomography (CT) and CT perfusion (CTP) simultaneously. Haematoma volume was measured on CT. The values of cerebral haemodynamic parameters including cerebral blood flow (CBF), cerebral blood volume (CBV), mean transit time (MTT), time to peak (TTP), and permeability–surface area product (PS) were measured in the perihaematomal region and the contralateral mirror region, and then relative values were calculated for statistical analysis. Linear regression was used to evaluate associations between BBB permeability and variables. RESULTS: A total of 87 ICH patients were included in this study. The focally elevated BBB permeability was observed in the perihaematomal region in ICH patients. Linear regression showed that reduced rCBF (β = –0.379, p= 0.001) and increased rCBV (β = 0.412, p= 0.000) correlated independently with increased relative PS (rPS) value in deep ICH, while only increased rCBV (β = 0.423, p= 0.071) correlated to increased rPS value in patients with lobar ICH. CONCLUSIONS: BBB permeability is focally elevated in the region around the haematoma. Cerebral haemodynamic alterations are associated with increased BBB permeability. Cerebral hypoperfusion may aggravate BBB compromise, and a compensatory increase in CBV may lead to reperfusion injury on BBB. Highlights: BBB permeability is focally elevated around the haematoma after ICH. Increased BBB permeability is associated with perihaematomal CBF and CBV. Decreased CBF may aggravate BBB compromise. A compensatory increase in CBV may lead to reperfusion injury on BBB.